2017
DOI: 10.1111/ans.13890
|View full text |Cite
|
Sign up to set email alerts
|

AdVance male urethral sling: medium‐term results in an Australian cohort

Abstract: Background Since 2008, the AdVance male urethral sling has emerged as a minimally invasive option for stress urinary incontinence. We aimed to evaluate the success of the AdVance sling using validated continence outcome measures. Methods A total of 72 patients treated with the AdVance sling completed validated questionnaires reporting on quality of life and functional outcomes. Incontinence was assessed according to pad weight, pad usage per day (PPD), International Consultation on Incontinence Questionnaire s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
2
10
0
3
Order By: Relevance
“…Rehder et al were able to show stable rates of 76.8% of cured patients after a follow‐up of 3 years for the AdVance sling system in a prospective trial. Papachristos et al could show a cure rate of 51% only after a median follow‐up of 52 months, indicating a decline of function over time. The suspected worsening of the continence status remained a major point of criticism and led to the introduction of the second generation of the transobturator retroluminal repositioning sling system, called AdVance XP.…”
Section: Discussionmentioning
confidence: 99%
“…Rehder et al were able to show stable rates of 76.8% of cured patients after a follow‐up of 3 years for the AdVance sling system in a prospective trial. Papachristos et al could show a cure rate of 51% only after a median follow‐up of 52 months, indicating a decline of function over time. The suspected worsening of the continence status remained a major point of criticism and led to the introduction of the second generation of the transobturator retroluminal repositioning sling system, called AdVance XP.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies assessed success of the AdVance sling utilizing questionnaires about improvements in everyday pad use and quality of life [38][39][40]. Papachristos et al [41] estimated the products of approved forms about quality of life and functional outcomes from a total of 72 men underwent the AdVance sling operation. The researchers reported that 37 patients (51%) were pad free or put on a defense pad, and 18 patients (25%) had a decline in daily pad use of ≥ 50%, during a median 52-month follow-up.…”
Section: Advance Sling (Boston Scientific)mentioning
confidence: 99%
“…Existen pocos trabajos en la literatura que hayan analizado los predictores con este dispositivo. Papachristos et al [389] comunicaron recientemente sus resultados con el dispositivo AdVance en una cohorte australiana de 72 pacientes con una edad media de 67 años y con un seguimiento de más de cuatro años. En este trabajo demostraron que los antecedentes de radioterapia pelviana previa y la incontinencia pre-operatoria severa se asociaron a peores resultados, pero no encontraron asociación con la edad.…”
Section: 7454slings Suburetralesunclassified
“…Este hallazgo está en concordancia con el resto de estudios publicados, como el de Friedl et al [391] o el de Lorenzo-Gómez et al [390] En tercer lugar, en nuestro trabajo el estadiaje pTNM se asoció a mejores resultados en los pacientes con mayor pTNM tratados En sexto lugar, los antecedentes de radioterapia previa se asociaron a peores resultados de continencia en pacientes tratados con cinta suburetral transobturatriz regulable, pero no con el resto de dispositivos. Friedl et al obtuvieron estos mismos resultados con ese dispositivo [391], sin embargo, el estudio de Papachristos et al no demostró asociación entre la historia de radioterapia previa y el éxito del implante de cintas suburetrales transobturatrices no regulables [389]. De todas formas, las revisiones sistemáticas realizadas como la de Ostrowski et al [394] han demostrado de forma clara que este antecedente se asocia a peores resultados, debido a la reducción de la vascularización por oclusión de pequeños vasos y a la fibrosis post-radioterapia [395] Finalmente, el análisis de la comorbilidad de los pacientes nos permitió observar una asociación entre la diabetes mellitus no insulinodependiente y el fracaso del tratamiento con cinta suburetral transobturatriz no regulable y con Remeex ® , no así entre la diabetes y el resto de dispositivos.…”
Section: 7454slings Suburetralesunclassified
See 1 more Smart Citation